Participation of the thalamic CM‐Pf complex in movement performance in patients with dystonia. Issue 9 (29th April 2016) - Semenova, Ulia; Raeva, Svetlana; Sedov, Alexey
ABSTRACT: Introduction: The centrum medianum‐ parafascicular complex of the human thalamus has a critical influence on cortical activity and significantly influences somatosensory function, arousal, and attention. In addition to its cortical connections, this region of the intralaminar thalamic nuclei is also connected to motor areas of the basal ganglia and the brain stem. Objective: The goal of this study was to identify movement‐related neurons in the centrum medianum‐parafascicular complex and analyze the changes in their activity during voluntary movements in patients with cervical dystonia. Methods: Single‐unit activity was recorded during the micro‐electrode‐guided surgical ablation procedures in patients with cervical dystonia. The neural responses and synchronous electromyographic signals of the neck and finger flexor muscles were simultaneously recorded. Results: We found the following 3 types of movement‐sensitive neurons in the centrum medianum‐parafascicular complex: neurons that responded selectively to voluntary hand movement (hand‐only neurons), neurons that selectively responded to neck movements (neck‐only neurons), neurons responding to both hand and neck movements (combined neurons). We discovered the following 3 patterns of movement‐related changes in neural activity: an increase in the firing rate, a reduction in the bursting activity, and short‐term oscillations and synchronization with neighboring neurons. The most pronounced and prolonged responses were observed during movements involving neck muscles as well as during involuntary dystonic movements. Conclusion: The centrum medianum‐parafascicular complex of the thalamus is a component of the subcortical network that participates in motor behavior and may be involved in the pathophysiology of cervical dystonia. © 2016 International Parkinson and Movement Disorder Society